Cream Skimming by Health Care Providers and Inequality in Health Care Access: Evidence from a Randomized Field Experiment - Anna Werbeck; Ansgar Wübker; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2020)
Using a randomized field experiment, we show that health care specialists cream-skim patients by their expected profitability. In the German two-tier system, outpatient reimbursement rates for both public and private insurance are centrally determined but are more than twice as high for the privately insured. In our field experiment, following a standardized protocol, the same hypothetical patient called 991 private practices in 36 German counties to schedule appointments for allergy tests, hearing tests and gastroscopies. Practices were 7% more likely to offer an appointment to the privately insured. Conditional on being offered an appointment, wait times for the publicly insured were twice as long than for the privately insured. Our findings show that structural differences in reimbursement rates lead to structural differences in health care access.
Keywords: I14; I11; I18; 330; health care inequality; reimbursement rates; health care access; discrimination; cherry picking; gastroscopy; audiometry; allergy test; allergists; otorhinolaryngologist; gastroenterologist